Work-life balance and employee commitment: mediating effect of job satisfaction - Inegbedion, Henry Egbezien (Frontiers in Psychology, 2024)
Introduction Work is very important to man and work experiences have implications on other aspects of human life. The major essence of work is to obtain resources to optimize other domains of life. This demands the need to strike a balance. Flowing from the positive and negative effect of the Spill over theory, the study investigated the influence of work-life balance (WLB) on employee job commitment using JS as the mediating variable. Methods A cross-sectional survey design elicited the desired data from 344 employees in 4 Universities and 4 multinational companies. Path diagram analysis served as the data analysis technique. Results/discussion The results show that all the family and religious lives have statistically significant negative influences on employee commitment (EMPC) while leisure and health have statistically significant positive influences on EMPC. The study thus, makes theoretical contributions.